2019
DOI: 10.1007/s40279-019-01068-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Motor Competence and Physical Fitness from Early Childhood to Early Adulthood: A Meta-Analysis

Abstract: Background: Motor competence and physical fitness are important factors for promoting positive trajectories of health over time. In 2008, Stodden and colleagues developed a model that discussed the role of both factors in physical activity. Furthermore, the authors hypothesized that the relationship between motor competence and physical fitness is reciprocal and changes over time. Objective: The aim of the present meta-analysis was to synthesize the evidence on the relationship between motor competence and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(172 citation statements)
references
References 54 publications
6
157
0
9
Order By: Relevance
“…These results are important as they suggest that the measures included in the KidFit Screening Tool (MSTP and SAMS), when used together, are valid indicators of health-and performance-related fitness, and are feasible for using in the KidFit Screening Tool for the purpose as suggested above. Additionally, despite the KidFit only being a screening tool, our findings were consistent with those of a recent systematic review with meta-analysis, which demonstrated a clear relationship between motor competence and physical fitness in children of varying ages, leading the authors to conclude that motor competence and physical fitness (including cardiorespiratory fitness) are important factors for promoting positive trajectories of health over time [31]. These statements further support the screening of these measures and offering intervention when required to ensure good health over time.…”
Section: Discussionsupporting
confidence: 90%
“…These results are important as they suggest that the measures included in the KidFit Screening Tool (MSTP and SAMS), when used together, are valid indicators of health-and performance-related fitness, and are feasible for using in the KidFit Screening Tool for the purpose as suggested above. Additionally, despite the KidFit only being a screening tool, our findings were consistent with those of a recent systematic review with meta-analysis, which demonstrated a clear relationship between motor competence and physical fitness in children of varying ages, leading the authors to conclude that motor competence and physical fitness (including cardiorespiratory fitness) are important factors for promoting positive trajectories of health over time [31]. These statements further support the screening of these measures and offering intervention when required to ensure good health over time.…”
Section: Discussionsupporting
confidence: 90%
“…In comparison, HRF in females is much more stable indicating that fitness levels attained by sixth class of primary school carry through into first year of second-level school. In addition, compared to MVPA which is a singular variable, HRF is a multifaceted construct [26,88]. Having high levels of HRF indicates that an individual displays fitness across a range of different activity-types (e.g., activities requiring CRE, MS and ME).…”
Section: Differences Between Males and Femalesmentioning
confidence: 99%
“…Low muscle strength, poor fundamental movement skills (FMS) and inadequate physical activity can interact synergistically to predispose youth to dynapenia and associated changes in contractile function and morphology of skeletal muscle [12,25,62]. Without regular opportunities to engage in strength-and skill-building activities during unstructured (e.g., outdoor play and recess) and structured (e.g., physical education and sport) events, school-age youth may be less likely to attain a level of muscular fitness and neuromuscular dexterity that are needed for ongoing participation in moderate to vigorous physical activities on the playground, in the gymnasium and at sport practice [54,72,77]. An understanding and appreciation of the interrelated factors that influence pediatric dynapenia may help to alter the current trajectory towards physical inactivity and related co-morbidities.…”
Section: Pediatric Dynapeniamentioning
confidence: 99%
“…Since FMS such as jumping, kicking and running serve as building blocks for more complex movement patterns, youth with poor FMS are more likely to have functional limitations and less likely to engage in regular physical activity and achieve desired levels of physical fitness [52,77]. Recent meta-analytic findings indicate that resistance training can have a positive impact on sprinting, jumping and throwing performance in youth [14,15] and others found a significant positive correlation between gains in FMS and the mean intensity of youth resistance training programs [8].…”
Section: Fig 1 Systemic and Causal Interactions Of The Factors That mentioning
confidence: 99%